Pengembangan Media Pembelajaran Untuk Pengenalan Sistem Pencernaan Manusia Menggunakan Teknologi Augmented Reality - Aldo Rizky Saputra; Herman Tolle; Muhammad Aminul Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The lack of interest in student learning and the less effective and interactive teaching and learning process is the impact of the lack of available facilities and infrastructure. In fact, only the guidebooks and LKS are supporting tools in the current teaching process. Augmented reality technology is a solution to help solve these problems. The 3D concept in AR technology can be applied in the world of education to develop abstract anatomical learning. By designing a mobile application the introduction of human digestion systems using the single marker method the author hopes to help the learning process and improve the quality of student learning in understanding the material provided by the instructor. Based on the results of effectiveness testing shows an increase of student learning outcomes of 10.25% which originally obtained average results from the pre-test of 75.75 to 85. By using the System Usability Scale method, usability testing points to satisfactory results. Based on the questions submitted to 10 respondents with an assessment weighting scale of 1 (Strongly Disagree) to 5 (Strongly Agree), the results of usability testing were 83.25 with Excellent and grade A ranking qualifications.